2018
DOI: 10.1038/s41467-018-03596-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent label-free quantitative detection of nano-sized bioparticles using a pillar array

Abstract: Disease diagnostics requires detection and quantification of nano-sized bioparticles including DNA, proteins, viruses, and exosomes. Here, a fluorescent label-free method for sensitive detection of bioparticles is explored using a pillar array with micrometer-sized features in a deterministic lateral displacement (DLD) device. The method relies on measuring changes in size and/or electrostatic charges of 1 µm polymer beads due to the capture of target bioparticles on the surface. These changes can be sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 55 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…With the development of DLD technology, there are multiple modes of DLD applications that are mostly demonstrated for medical and biological research applications, including the particle separation, concentration, buffer exchange, and [23] label-free detection. Initially, DLD uses the particle size parameter for the basis of the separation.…”
Section: Dld Applicationsmentioning
confidence: 99%
“…With the development of DLD technology, there are multiple modes of DLD applications that are mostly demonstrated for medical and biological research applications, including the particle separation, concentration, buffer exchange, and [23] label-free detection. Initially, DLD uses the particle size parameter for the basis of the separation.…”
Section: Dld Applicationsmentioning
confidence: 99%
“…Amongst the fluid-mediated surface interactions between solids, electrostatic forces are expected to be of primary importance. In the specific context of DLD devices, recent articles by Zeming et al [33,34] showed that particle-obstacle electrostatic interactions can significantly impact the dynamics of suspended particles in DLD arrays. These interactions originate from the existence of an Electric Double Layer (EDL) at the solid-fluid interface.…”
Section: Electrostatic Forcesmentioning
confidence: 99%
“…The microfluidics DLD based on the asymmetrical gap with a lateral gap of 9 µm and downstream gap of 3 µm from our previous work was used to demonstrate the microbeads separation and detection on the smartphone platform (Figure 9, Supporting Information). [21,47,48] The device was made from PDMS material and fabricated through soft lithography process from SU-8 on silicon master mold. [21,47,48] The device was made from PDMS material and fabricated through soft lithography process from SU-8 on silicon master mold.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%